HUBUNGAN RIWAYAT KELUARGA DENGAN KEJADIAN DISMENORE PADA SISWI KELAS 3 SMP FULLDAY SCHOOL AL-MUHAJIRIN KABUPATEN PURWAKARTA TAHUN 2021 - Virsha Nova Renatha (2022)
Dysmenorrhea is a uterine pain during menstruation manifesting cyclical lower abdominal or pelvic pain, which may also radiate to the back and thights, usually takes palce after 6-24 months of menarche. It causes significant disruption in quality of life and can result in absenteeism. In Jawa Barat, it is estimated that about 54,9% of adolescent experienced dysmenorrhea. Family history is a risk factor that can increase the likelihood of dysmenorrhea. This study aimed to prove the relationship between family history and dysmenorrhea in the 3rd grade students of Al-Muhajirin Junior High School, in Purwakarta Regency, 2021. This research used obervasional analytical methods with a cross sectional approach. The sample in this study amounted to 56 respondents. Sampling using total sampling. Data analysis includes univariate and bivariate analysis using Chi-Square statistical test. The result of this study indicate that of the 56 respondents studied, there were 69,6% respondents had dysmenorrhea, 41,1% respondents had mild pain of dysmenorrhea level and 58,9% respondents had a family history. Based on the results of the analysis, it was found that p value = 0.001 which indicates that there is a relationship between family history and dysmenorrhea in the 3rd grade students of Al-Muhajirin Junior High School, in Purwakarta Regency,2021 andO R = 9.425, meaning that students with a family history have a probability of experiencing dysmenorrhea as much as 9,425 times. This is due to genetic factors or because cauanatomical and physiological condition of a person in general are almost the same as parents and siblings.